Analyzing Indonesian Football Sentiment Towards PSSI Performance Using Support Vector Machines - Hakim, Faturrahman; Astuti, Yuli (Journal of Intelligent Software Systems, 2024)
Football is a popular and widely engaged sport in Indonesia, attracting individuals across various age groups, including teenagers, adults, and children. The Indonesian Football Association (PSSI), established on April 19, 1930, originally named the All-Indonesian Football Association, is the governing body responsible for managing and overseeing football activities in the country. Despite its long history, PSSI has faced significant criticism for its perceived lack of professionalism in handling and managing Indonesian football. This discontent was notably amplified in the wake of the cancellation of the U-20 World Cup, leading to a surge of negative sentiments on social media platforms, particularly Twitter. This study aims to analyze public opinion regarding PSSI's performance. Public opinion, which emerges in response to various events, tends to be diverse due to the differing perspectives of individuals. The research focuses on assessing the balance between positive and negative sentiments towards PSSI's performance. By employing a comprehensive approach to sentiment analysis, including stages such as data preprocessing, labeling, modeling, and evaluation, this study provides a detailed examination of public sentiment. The methodology involves the application of the Support Vector Machine (SVM) algorithm across four tests with different data splits and the use of the SMOTE technique to address class imbalance. The findings reveal that the fourth test yielded the most effective results in sentiment classification, achieving an accuracy of 70.75%, precision of 67.16%, recall of 68.18%, and an F1 score of 67.66%